2022
DOI: 10.3390/molecules27051732
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Different Winemaking Protocols to Mitigate Smoke Taint Character in Wine

Abstract: There is an increase in the levels of volatile phenols in wine made with smoke-impacted grapes. These compounds are present in wood smoke resulting from the pyrolysis (thermal decomposition) of lignin and at high levels give overpowering smoky and ashy characters to a wine. This research aimed to compare all the suggested wine mitigation strategies that evolved from prior research using smoke-impacted grapes under identical winemaking conditions except for the parameter under investigation. Cabernet Sauvignon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…All samples were assessed in duplicate in a complete block design. Te judges were forced to have a 2-minute rest between each sample and a 10-minute rest between sets of two and three samples, to minimise carryover [27,28]. Water was provided for palate cleansing.…”
Section: Basic Chemical Compositionmentioning
confidence: 99%
“…All samples were assessed in duplicate in a complete block design. Te judges were forced to have a 2-minute rest between each sample and a 10-minute rest between sets of two and three samples, to minimise carryover [27,28]. Water was provided for palate cleansing.…”
Section: Basic Chemical Compositionmentioning
confidence: 99%
“…Similar to the duration gradient, ketones (11 kinds), phenols (11 kinds) and aldehydes (five kinds) were the main VOCs. Phenolic substances were mainly produced by a gradual decomposition of lignin and were unique volatile flavor substances in smoking [ 42 ]. It was mainly reflected in the generation of VOCs during the heating and decomposition of smoking substances, as well as phenolic substances formed after smoking [ 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…A wine is seen as smoke impacted or tainted when there is an overpowering smoky, medicinal, chemical, burnt, or ashy aroma on the nose and a distinctive retronasal ash tray-like character in the mouth [1]. Currently there are no effective remedial actions available to the industry for smoke impacted grape juice and wine resulting in devastating losses when wildfires occur [2,3]. Research has shown that during wildfires substantial amounts of volatile phenols (VP's) are released into the air from wood burning through the pyrolysis (thermal decomposition) of lignin.…”
Section: Introductionmentioning
confidence: 99%